Differential effects of caffeine, acute aerobic exercise, and placebo on mental fatigue - Ali Shirzad; Nathan Frewen; Anisa Morava; Nader Elshawish; Harry Prapavessis (PLoS ONE, 2026)
Mental fatigue negatively affects the productivity and health of the general population. Mental fatigue manifests following sustained mental activity and is defined by subjective feelings of inhibition and objective decrements in mental performance. Caffeine is one of the most common stimulants used to mitigate mental fatigue. However, regular caffeine consumption may be associated with several side effects and potential dependence. The efficacy of acute aerobic exercise as an alternative mental fatigue intervention remains ambiguous. Thus, the present study utilized a randomized crossover design to compare the efficacy of the three treatments in mitigating mental fatigue in 26 adult caffeine consumers. The three treatments included: 1) 20 minutes of moderate-intensity cycling, 2) consumption of 2.5 mg/kg of caffeine, and 3) consumption of placebo (0.67 g corn starch). Treatments were administered prior to a mental fatigue-induction task (30-minute Stroop task). Participants and the experimenter were both blinded to the administration of caffeine or placebo. Objective (Psychomotor Vigilance Task) and subjective (visual analog scales) mental fatigue measures were taken prior to and following the mental fatigue-induction task. We hypothesized that in the placebo condition, participants would demonstrate greater mental fatigue following a 30-minute Stroop task relative to baseline. Further, mental fatigue induction will be mitigated in the acute exercise and caffeine consumption conditions to a similar degree. Participants reported significantly greater mental fatigue following a 30-minute Stroop task (p < 0.001, d = −0.735). Comparison of the placebo and caffeine consumption did not exhibit a reliable difference (all p’s > 0.05). Contrary to our hypothesis, mental fatigue was not mitigated following acute exercise (p = 0.499). Further investigations are warranted to explore the potential of varying exercise intensities and durations in mitigating mental fatigue.